VD_FINDINFO Arrêt / 2013 / 243 vom 16. Mai 2013 - VD Tribunal cantonal (2013)
RÉDUCTION DES PRIMESAM, OBLIGATION DE RENSEIGNER, RESTITUTIONEN GÉNÉRAL | 65 LAMal, 11 LVLAMal, 12 LVLAMal, 21a LVLAMal, 31 LVLAMal, 32 LVLAMal, 9 LVLAMal, 23 al. 2 RLVLAMal, 26 RLVLAMal